Assessing Nurses' Workplace Social Capital: A Study Protocol for Culturally Appropriate Instrument Development. (24th September 2022) - Xu, Jia-Min; Stark, Azadeh; He, Yi-Zhu; Ying, Bi-He; Chen, Min-Hua; Lian, Zheng-Mei; Huang, Yang-Sheng; Chen, Rui-Ming; Chen, Yuan-Yuan; Shang, Xu-Li; Li, Chun-Ying; Yang, Dong-Liang; et al.
Workplace social capital positively influences the quality but reduces the cost of healthcare services. Academic research suffers from limited and inadequate culturally sensitive nurses' workplace social capital instruments. Here we report on the design and protocol of a culturally focused instrument development study in China. The overarching objective of our dual phase study is to develop and validate a questionnaire measuring nurses' workplace social capital tailored toward Chinese cultural values and norms. In the first phase of INSTRUMENT DEVELOPMENT, the qualitative phase, we will conduct interviews with purposefully sampled nurses from five geographically diverse regions capturing 16 provinces in China to formulate the initial version of the Nurses' Workplace Social Capital Questionnaire (NWSCQ). Data collection will be stopped at the saturation point and content analysis will be performed for interview data in parallel. The initial version of the NWSCQ will be evaluated and confirmed by two-rounds of expert consultation (target N = 20) and pre-tested among 70 nurses. During the second phase of INSTRUMENT VALIDATION or the quantitative phase, we will validate the psychometric properties of the NWSCQ. The validity and reliability of the questionnaire will be examined and validated through three cross-sectional surveys among nurses (target N = 1154) randomly selected from 12 tertiary hospitals. We have reported our study protocol with the intention of sharing our experience with researchers in other countries who are striving to advance the phenomenon of culturally sensitive and social normatively appropriate nurses' workplace social capital. Findings from our study should advance the development of culturally appropriate and valid instrument of nurses' workplace social capital, another important step toward recognition and incorporation of cultural diversity in the daily operation of healthcare industry.